Comparison of the Perioperative and Postoperative Effects of Levobupivacaine and of Levobupivacaine + Adrenaline in Pediatric Tonsillectomy: A Double-Blind Randomized Study - Faruk Cicekci; Cigdem Sizer; Sait Selcuk Atici; Sule Arican; Adnan Karaibrahimoglu; Inci Kara (Pain Research and Management)
Objectives. We aimed to assess the effects of levobupivacaine and of levobupivacaine + adrenaline administered during pediatric tonsillectomy on the postoperative period. Methods. A total of 90 patients between the ages of five and twelve were divided randomly into two groups before tonsillectomy: levobupivacaine only (0.5%) 0.4 mg·kg−1 or levobupivacaine (0.5%) 0.4 mg·kg−1 + adrenaline (1 : 200.000) administered by means of peritonsillar infiltration. Primary outcomes were postoperative pain scores recorded at various intervals until 24 hours postoperatively. Secondary outcomes included postoperative nausea and vomiting (PONV), time to first oral intake, time to the first administration of analgesics and total consumption of analgesics, and the amount of bleeding for all children. Results. In both groups, patients had the same postoperative pain scores and PONV rates, and equal amounts of analgesics were consumed up to 24 hours postoperatively. The two groups also had the same time until first oral intake, recovery time and time to the first analgesic request, and amount of bleeding. Conclusions. Perioperative levobupivacaine infiltration on its own is a valid alternative to the combination of levobupivacaine + adrenaline for perioperative and postoperative effectiveness in pediatric tonsillectomy. This trial is registered with Australian New Zealand Clinical Trial Registry ACTRN: ACTRN12617001167358.